Answer:
see explanation
Step-by-step explanation:
Given the 2 equations
3x - 5y = - 2 → (1)
2x + y = 3 → (2)
Multiply (2) by 5 will eliminate y when added to (1), that is
10x + 5y = 15 → (3)
Add (1) and (3) term by term
(3x + 10x) + (- 5y + 5y) = (- 2 + 15)
13x = 13 ( divide both sides by 13 )
x = 1
Substitute x = 1 into (2) for corresponding value of y
2 + y = 3 ⇒ y = 3 - 2 = 1
Solution is (1, 1)
Use a calculator called symbolab.com
The +2 goes on the Y-Axis… From
the 2 count up 3 times and go to the right 2 times
Answer:
20
Step-by-step explanation:
Cause im smart and you should trust me. duh
Answer: A. An OPEN circle on the number 5 and an arrow shading to the RIGHT.